Front-of-pack health imagery on both 'healthy' and 'unhealthy' foods leads people to misremember seeing health claims: Two memory experiments. (1st July 2022) - Delivett, Christopher P.; Farrow, Claire V.; Thomas, Jason M.; Nash, Robert A.
Abstract: Front-of-pack health imagery can shape people's inferences about food products' health benefits, even leading people to falsely remember reading health claims they never saw. However, research has typically examined these effects in situations where participants have little contextual information to guide their inferences about a product. The present research aimed to replicate the finding that front-of-pack health imagery leads participants to falsely remember reading health claims. It also extends that finding, by exploring whether this effect is moderated by the presence of contextual information signaling the product's actual 'healthiness'. In two pre-registered experiments, participants saw images of fictitious food products accompanied by written nutrition claims. Some of the products contained a health-related image whereas others did not. The supposed 'healthiness' of each product was manipulated by altering the color of the products' multiple traffic light (MTL) label (Experiment 1), or with an explicit healthiness statement (Experiment 2). Participants then attempted to remember the written claims that had appeared on each product's packaging. Health-related images increased participants' tendency to falsely remember reading health claims. But this was true regardless of whether or not participants saw contextual cues about the products' healthiness, either indirectly (Experiment 1) or directly (Experiment 2). These findings suggest that the presence of health imagery on a food product's package can lead consumers to infer health benefits, even when other, more direct cues indicate that the product is unhealthy. This research informs debates on safeguarding consumers from potentially misleading health claims, through the regulation of imagery in food marketing.